2015
DOI: 10.2147/copd.s85681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating inhaler use technique in COPD patients

Abstract: BackgroundPoor inhalation techniques are associated with decreased medication delivery and poor disease control in chronic obstructive pulmonary disease (COPD). The purpose of this study was to evaluate techniques for using inhaler devices in COPD patients.MethodsA prospective cross-sectional study was conducted to assess patient compliance with correct techniques for using inhaler devices across four regimens, ie, the pressurized metered-dose inhaler (pMDI), the pMDI with a spacer, the Accuhaler®, and the Han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
144
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(164 citation statements)
references
References 33 publications
14
144
4
2
Order By: Relevance
“…Some studies have shown that literacy rate of patients is not associated with the correct technique, 11,19 whereas other studies have shown that education level does have an impact on the inhaler technique. 4,7,13 There was also no significant difference in the technique between asthmatics and the COPD patients, which could be because the number of COPD patients (n=42) when compared to asthmatics (n=200) were less in our study. The improvement in asthmatics in the follow up visit was found to be more significant when compared to the COPD patients.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Some studies have shown that literacy rate of patients is not associated with the correct technique, 11,19 whereas other studies have shown that education level does have an impact on the inhaler technique. 4,7,13 There was also no significant difference in the technique between asthmatics and the COPD patients, which could be because the number of COPD patients (n=42) when compared to asthmatics (n=200) were less in our study. The improvement in asthmatics in the follow up visit was found to be more significant when compared to the COPD patients.…”
Section: Discussioncontrasting
confidence: 49%
“…9 Problems with inhaler techniques were recognised shortly after the launch of pMDIs in the 1960s and reviews show that incorrect inhaler technique is unacceptably frequent and has not improved over the past 40 years. 10 Furthermore, incorrect technique has been reported in up to 94% of patients 4,8,[11][12][13] and poor technique was estimated to be prevalent in an average of 50% of cases. 14 The main advantages of inhaler devices over oral tablets for chronic respiratory diseases include lower dose, rapid onset of action, desired local action and no gastric or systemic adverse drug reactions.…”
mentioning
confidence: 99%
“…A study conducted by Pothirat et al found that for the pMDI, the steps "breathe out gently to residual volume" and "shake inhaler thoroughly" were most frequently performed incorrectly. 24 For the pMDI with spacer, the step "breathe in and out through mouthpiece at least three times" was most frequently performed incorrectly.…”
Section: Agementioning
confidence: 99%
“…Many patients use more than one inhaler and are thus required to learn multiple different sets of instructions. Over 90% of COPD patients do not use their inhalers correctly, [7][8][9][10] and errors in use are associated with worse symptoms and increased hospitalizations. 11 Because of this, COPD guidelines recommend inhaler teaching and review at clinic visits and on discharge from the hospital after an exacerbation.…”
Section: Introductionmentioning
confidence: 99%